2019
DOI: 10.1109/trpms.2018.2828083
|View full text |Cite
|
Sign up to set email alerts
|

Modeling “Textured” Bones in Virtual Human Phantoms

Abstract: The purpose of this study was to develop detailed and realistic models of the cortical and trabecular bones in the spine, ribs, and sternum and incorporate them into the library of virtual human phantoms (XCAT). Cortical bone was modeled by 3D morphological erosion of XCAT homogenously defined bones with an average thickness measured from the CT dataset upon which each individual XCAT phantom was based. The trabecular texture was modeled using a power law synthesis algorithm where the parameters were tuned usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…[43][44][45] Similar approaches have been implemented to incorporate intraorgan structures for other organs such as the liver, [46][47][48] brain, [49][50][51] heart, [52][53][54] and bones. [55][56][57] Recently, some studies have showed that deep learning approaches, such as generative adversarial network (GAN) models, can synthesize images that have similar visual and statistical features of a set of training input data. 58,59 These techniques can also be utilized for the purpose of modeling intraorgan heterogeneities within the organs and structures of computational phantoms, particularly for the parenchymal regions where organs usually have "textural" appearances.…”
Section: Modeling Intraorgan Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…[43][44][45] Similar approaches have been implemented to incorporate intraorgan structures for other organs such as the liver, [46][47][48] brain, [49][50][51] heart, [52][53][54] and bones. [55][56][57] Recently, some studies have showed that deep learning approaches, such as generative adversarial network (GAN) models, can synthesize images that have similar visual and statistical features of a set of training input data. 58,59 These techniques can also be utilized for the purpose of modeling intraorgan heterogeneities within the organs and structures of computational phantoms, particularly for the parenchymal regions where organs usually have "textural" appearances.…”
Section: Modeling Intraorgan Structuresmentioning
confidence: 99%
“…[305][306][307] Abadi et al 141,308 characterized the noise texture across filtered back projection and iterative reconstruction algorithms. In this study, an XCAT phantom 41,55 was imaged 50 times using a validated CT simulator, setup to mimic the parameters and settings of a specific scanner model (Siemens Definition Flash). The simulated images were reconstructed with both filtered backprojection and iterative reconstruction algorithms using a commercial software.…”
Section: Ct Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…A textured XCAT phantom [13], [14], [16] was imaged 50 times using DukeSim, based on the properties of a commercial scanner (Somatom Definition Flash; Siemens Healthcare) 120 kV and a pitch of 1.0. Projection images were reconstructed using a commercial reconstruction software (Siemens ReconCT) with filtered backprojection (FBP, kernel of B31f) and iterative (SAFIRE, kernel of I31f) algorithms.…”
Section: H Pilot Vctmentioning
confidence: 99%
“…On the patient side, there have been extensive efforts in developing populations of anthropomorphic phantoms that model highly detailed organ anatomies [1]- [7] with intraorgan heterogeneities in the breast [8]- [12], lungs [13], [14], liver [15], and bones [16].…”
Section: Introductionmentioning
confidence: 99%